Digital Financial Ethics and Risk Management - Supandi, Hanie; Irawan, Yopie; Setiawati, Dwi; Kurniawan, Rusdi; Lestari, Bunga Westu; Permatasari, Delsa Yunia; Marjohan, Masno (International Journal of Economics, Management and Accounting (IJEMA), 2025)
The rapid development of digital technology has transformed the global financial industry landscape, bringing efficiency but also increasing the complexity of risks such as cyber attacks, data breaches, and regulatory non-compliance. This study aims to evaluate risk management strategies in digital finance and the importance of integrating ethical values through a literature review approach. Data was collected from national journals and relevant academic articles, focusing on training, technology implementation, and risk management policies. The findings indicate that effective strategies require adaptive technology-based approaches, such as the implementation of Artificial Intelligence (AI), blockchain, and the Internet of Things (IoT). Dominant digital risks include fraud, data breaches, and system attacks, which demand ethics-based governance and improved digital literacy. Internal factors such as human resources and organisational culture, as well as external factors such as regulations and fintech competition, also influence the effectiveness of risk management. In conclusion, the success of risk management in digital finance is determined by the synergy between technological sophistication and the comprehensive application of ethical principles in the governance of financial institutions.